Kerja Sama Pembangunan Korea Selatan di Vietnam dalam Pengembangan Area Pedesaan melalui Model Saemaul Undong - Lestari, Indah (Global: Jurnal Politik Internasional, 2016)
In this last decade, a closed cooperation of rural development “Saemaul Undong” between South Korea and Vietnam has been formed. Saemaul Undong is a success model of South Korea’s rural development. Along with it, question related to the possibility of adopting Saemaul Undong by developing countries arises. With this regard, this research attempts to explain the reasons why this cooperation has been formed. By using concept of cooperation, this research tries to observe the existence of goals and benefits in “Saemaul Undong” cooperation between South Korea and Vietnam. Result of this research affirmed that goals and benefits spurred “Saemaul Undong” cooperation between both parties. South Korea aimed to internationalized its Saemaul Undong, while Vietnam aimed to attain the success of rural development. In this context, South Korea was able to provide funding, experience, and knowledge in mobilizing rural people’s participation, while Vietnam was able to justify the possibility of adopting SU by developing countries. Finally, this research showed that cooperation can not be separated from goals and benefits of parties.